Diametral theory of algebraic surfaces and geometric theory of invariants of groups generated by reflections. II - Ignatenko, V. F. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We systematically present the basic principles of the geometric theory of invariants of infinite groups generated by skew reflections with respect to hyperplanes in the real Euclidean space.